Ikasekin: design of an holistic learning model for the development of entrepreneurial competence - Zorrilla Calvo, Pilar; Rincón Díez, Virginia; Sáiz Santos, María (Journal of Management and Business Education, 2020)
Progress in the development of key educational competencies for labor insertion and entrepreneurship in our society, such as creativity, innovation and entrepreneurship, are being very numerous in recent decades. Teachers are promoting programs to implement new methodologies for achieving this goal. However, the university community lacks validated methodologies with measurement of results in the medium and long term. The aim of this paper is to present the validation methodology of the teaching method we have agreed to call IKASEKIN, to achieve educational competence "Ability to develop Creativity, Innovation and Entrepreneurship" in the university environment. This method has been implemented in the Marketing degree of the University of the Basque Country UPV/EHU. The results show that the entrepreneurial capacity of the students, after taking two subjects through Project Based Learning in the second year, is strengthened over time when taking a course directly involved with the entrepreneurship in the fourth year.